ANALYSIS OF MICROSCOPIC WEAR ON STRAIGHT GEAR WITH ROTATION VARIATION - Febri Putra Perdana; Darto Darto; I Made Sunada (University of Merdeka Malang, 2019)
Wear is an important factor in reducing the function of engine performance including limiting the service life and performance of various engine components that rub against each other directly, this results in increased maintenance costs. In this study aims to determine the rate of straight gear wear with SCM 440 material from the influence of load and shaft rotation. Experimental research methods with variables of 200 rpm, 500 rpm and 1000 rpm and load respectively 0, 5, 10 kg, from the test results obtained the highest value of power at 1000 rpm and 0 kg load, while for the lowest wear value obtained at 200 rpm and a load of 5 kg, this is due to the misalignment factor in the drive shaft and being driven, this can be seen from the average wear position located at the end of the gear that is in direct contact between the gear and the gear is moved, so that in rotation high and without loading the shaft rotation is not balanced, but at high rotation and with a certain load imbalance rotation due to misalignment can be suppressed and produce a low wear value.